Evaluation Of Melatonin Effects On Retinopathy Of Prematurity Prophylaxis (Journal of Pharmaceutical Negative Results, 2023)
Background: According to the latest evidence, infants with gestational age < weeks (33 weeks and six days or less) or birth weight ≤ 2,000 grams are at risk of prematurity retinopathy (ROP) and should be screened. It is preventable in most cases and treatable if diagnosed on time; otherwise, the disease is progressive and quickly leads to blindness. In the final stages of the disease, treatment is complicated and, in some cases, impossible and expensive.Therefore, this study was conducted to evaluate the early diagnosis and treatment of this disease and the prophylactic effect of melatonin.Methods: This study was a clinical trial conducted on all preterm infants admitted to the neonate intensive care unit (NICU) ward of Akbarabadi and Ali Asghar hospitals of Iran University of Medical Sciences. Study information was given to the parents, and they were included in the study after obtaining written consent. These infants were randomly divided into two groups; for the first group, melatonin (3 mg/kg/day) was administered from day 7 of birth to the end of week 37, and the second group (control group) did not receive this drug. After completing the course, the two groups were evaluated and compared regarding the incidence of retinopathy prematurity.Results: Sixteen neonates in two groups were included in this study. Between the two groups, there was not any significant difference in neonatal gender (P=0.6), mean gestational age (P=0.6), birth weight (P=0.7), average APGAR score in minutes 1 (P=0.3) and five (P=0.1), umbilical cord PH (P=0.8), mechanical ventilation and CPAP (P=0.4), other respiratory support (P=0.7), duration of hospitalization (P=0.7), final weight (P=0.7). 13.3% of neonates in the melatonin group and 36.7% of the control group had ROP. There was a significant difference in the incidence of ROP according to the study group (P=0.03). However, there was no significant relationship between the study group and the severity of neonatal ROP (P=0.9).